Efektivitas Program Makan Gratis pada Status Gizi Siswa Sekolah Dasar: Tinjauan Sistematis - Natalia Desiani; Ahmad Syafiq (Malahayati Nursing Journal, 2025)
ABSTRACT Optimal nutritional status is a fundamental factor in ensuring healthy growth and development, particularly among elementary school students. Malnutrition, in the form of stunting or overweight, adversely affects children’s health and academic performance, leading to significant long-term consequences. School feeding programs have been implemented in various countries as interventions to improve access to nutritious food for students. This systematic review aims to explore the effectiveness of school feeding programs in enhancing the nutritional status of students. The research encompasses studies published between 2014 and 2024, evaluated through a search of the PubMed, Scopus, and ProQuest databases. Inclusion criteria consisted of randomized controlled trials, observational studies, and meta-analyses, adhering to PRISMA guidelines. The review identified 12 articles demonstrating that school feeding programs significantly improve nutritional status, including increases in Body Mass Index (BMI) and reductions in the prevalence of anemia among elementary school students. This study concludes that school feeding programs provide substantial benefits in enhancing students' nutritional status, with positive impacts on BMI and a decrease in anemia prevalence.  Keywords: Free School Meals Program, Primary School Students, Body Mass Index (Bmi), Anemia  ABSTRAK Status gizi yang optimal adalah faktor fundamental untuk memastikan pertumbuhan dan perkembangan yang sehat, terutama pada siswa sekolah dasar. Malnutrisi, baik dalam bentuk stunting maupun kelebihan berat badan, berdampak negatif terhadap kesehatan dan kinerja akademik anak, serta dapat mengakibatkan konsekuensi jangka panjang. Program makan gratis di sekolah telah diterapkan di berbagai negara sebagai intervensi untuk memperbaiki akses terhadap makanan bergizi bagi siswa. Tinjauan sistematis ini bertujuan untuk mengeksplorasi efektivitas program makan gratis di sekolah dalam meningkatkan status gizi siswa. Penelitian ini mencakup studi yang diterbitkan antara tahun 2014 - 2024, yang dievaluasi melalui penelusuran di database PubMed, Scopus, dan ProQuest. Kriteria inklusi mencakup penelitian yang menggunakan uji acak terkendali, studi observasional, dan meta-analisis, mengikuti pedoman PRISMA. Hasil penelitian menghasilkan 12 artikel yang menunjukkan bahwa program makan gratis secara signifikan meningkatkan status gizi, termasuk peningkatan Indeks Massa Tubuh (IMT) dan penurunan prevalensi anemia pada siswa sekolah dasar. Kesimpulan penelitian ini adalah program makan gratis di sekolah memberikan manfaat signifikan dalam memperbaiki status gizi siswa, termasuk peningkatan IMT dan penurunan prevalensi anemia. Kata Kunci: Program Makanan Gratis Di Sekolah, Siswa Sekolah Dasar, Indeks Massa Tubuh (Imt),Anemia